2001
DOI: 10.1080/02786820152546798
|View full text |Cite
|
Sign up to set email alerts
|

Hygroscopic Study of Glucose, Citric Acid, and Sorbitol Using an Electrodynamic Balance: Comparison with UNIFAC Predictions

Abstract: The equilibrium water sorption and desorption characteristics of three pharmaceutical excipients, namely, glucose, citric acid, and sorbitol, were investigated at 25 ± C using an electrodynamic balance (EDB). The mass fraction of solute (mfs), de ned as the ratio of the dry solute mass to the solution mass, of the additives was measured as a function of relative humidity (RH) at equilibrium. Bulk measurements and literature data suggest that these three additives all crystallize at their respective saturation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
72
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 24 publications
7
72
0
Order By: Relevance
“…Water activities of citric solutions were determined by the isopiestic and isotenoscopic methods [89,93] and recently by applying the electronic hygrometer [144][145][146][147][148], the electrodynamic balance (EDB) [144] and the hygroscopicity tandem differential mobility analyzer (HTDMA) [149]. By using EDB and HTDMA equipment, the hygroscopicity cycles including hydration and dehydration of solid particles can be observed.…”
Section: Thermodynamic Properties Of Aqueous Solutions Of Citric Acidmentioning
confidence: 99%
See 2 more Smart Citations
“…Water activities of citric solutions were determined by the isopiestic and isotenoscopic methods [89,93] and recently by applying the electronic hygrometer [144][145][146][147][148], the electrodynamic balance (EDB) [144] and the hygroscopicity tandem differential mobility analyzer (HTDMA) [149]. By using EDB and HTDMA equipment, the hygroscopicity cycles including hydration and dehydration of solid particles can be observed.…”
Section: Thermodynamic Properties Of Aqueous Solutions Of Citric Acidmentioning
confidence: 99%
“…Such measurements were performed in the context of hygroscopic properties of pharmaceutical solids, atmospheric aerosols and foodrelated solutions. Vapour pressures of water over citric acid solutions at 25 °C are known for different concentration ranges from investigations of Levien [89], Apelblat et al [93], Velezmoro and Meirelles [145,146], Peng et al [144], Maffia [147,148] and Zardini et al [149]. Velezmoro [146] measured water activities at 30 and 35 °C, Apelblat et al [93] from 30 to 45 °C, and few results exist also at 26.5 °C which were determined by Chirife and Fontan [150].…”
Section: Thermodynamic Properties Of Aqueous Solutions Of Citric Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…We also show data for glucose and fructose for comparison with our HTDMAderived estimates. Peng et al (2001b) suspended drops of aqueous solutions of glucose at controlled RH in an electrodynamic balance and deduced composition from particle mass measurements. Bhandari and Bareyre (2003) used a water activity meter with a sensitivity of 0.001.…”
Section: Levoglucosanmentioning
confidence: 99%
“…12. The fit for water activity for glucose solutions suggested by Peng et al (2001b) is not used, as the reported water activity polynomials are only valid for a w <0.98.…”
Section: Levoglucosanmentioning
confidence: 99%